Pembentukan Karakter Islami Remaja Melalui Pengajian Rutin di Madrasah Desa Cimeong Banjaran Majalengka - Kholiq, Dani abdul (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2023)
This article analyzes the important role of Islamic character education in shaping the character of teenagers through regular religious study activities in the Cimeong Village Madrasah in Banjaran Majalengka. Islamic character education is an educational approach aimed at developing moral and ethical values based on the teachings of Islam. Character formation is a crucial aspect in facing the social and moral challenges encountered by teenagers in the modern era. In this context, the regular religious study activities in the Cimeong Village Madrasah in Banjaran Majalengka play a central role as a means of character formation. In the context of the Cimeong Village Madrasah in Banjaran Majalengka, regular religious study activities become an effective tool for educating Islamic character among teenagers. This article also discusses the important role of educators and parents in supporting this character formation process. By utilizing interactive and applicable teaching methods, regular religious study activities are able to create a positive environment and support the development of Islamic character in teenagers. This character education not only equips teenagers with religious knowledge but also helps them internalize the values of goodness in their daily lives.